Ideas of enterprise informationization based on user experience - Feng CHEN; Tongfei XIA; Dongshu YANG (Dianxin kexue)
On the purpose of solving the problems of the traditional modes，such as difficult to realize the user personalized design，tough to fuse data，and unable to respond to the user demand，some ideas of construction mode for experience informationization based on user experience were presented.Extending from the traditional enterprise informatization，the new mode based on the massive amounts of data.The new mode uses the data asset-like management for guarantee，and uses the service-oriented data processing method for support，to achieve the user experience application，which is form an end user perspective.In the end，a typical application scenario including data trading platform，data asset-like management，high-speed computing service，and public platform，was put forward.